Disturbance Observer-Based Robust Control of a Quadrotor Subject to Parametric Uncertainties and Wind Disturbance - Benevides, Joao R. S.; Paiva, Marlon A. D.; Simplicio, Paulo V. G.; Inoue, Roberto S.; Terra, Marco H. (IEEE access, 2022)
We propose a disturbance observer-based controller to deal with the trajectory tracking problem of a quadrotor subject to parametric uncertainties and wind disturbance. The design is based on the combination of a recursive robust linear-quadratic regulator and a Kalman filter. Robust regulation deals with uncertainties of state and input matrices of the quadrotor in order to minimize, mainly, its trajectory tracking error. Filtering aims to estimate wind disturbance based on an augmented state-space model of the quadrotor. We finish the approach with a compensation controller whose task is to perform disturbance attenuation. We develop indoor experiments where a wind disturbance source provides a measurable speed pattern. We provide a comparative study among the robust control approach proposed with a feedback linearization controller, a proportional-integral-derivative controller, and a nominal linear-quadratic regulator.